2004
DOI: 10.1002/chem.200305467
|View full text |Cite
|
Sign up to set email alerts
|

Road Maps for Nitrogen‐Transfer Catalysis: The Challenge of the Osmium(VIII)‐Catalyzed Diamination

Abstract: Although the Sharpless dihydroxylation has been used on laboratory and industrial scales for several decades, an analogous osmium-catalyzed diamination is unknown. To explore the reaction of osmium(VIII) oxo-imido complexes with C=C bonds, density functional calculations have been performed. The calculations predict a chemoselective and perispecific [3+2] addition of the NH=Os=NH moiety of diimidodioxoosmium(VIII) to ethylene, yielding dioxoosma-2,5-diazolidine. At first sight, this metallacycle seems extremel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 98 publications
2
31
0
Order By: Relevance
“…Deubel and MuÇiz recently reported theoretical studies of the reaction pathways of the addition of [OsO 2 (NH) 2 ] to ethylene. [5] The calculations predict that the three possible [3+2] addition reactions are kinetically and thermodynamically favored over the two [2+2] additions, and that the diamination should be the most favored reaction. Pioneering experimental studies of the diamination of olefins with osmium trisimido compounds [OsO (NR) 3 ] have recently been reported by MuÇiz.…”
Section: Introductionmentioning
confidence: 98%
“…Deubel and MuÇiz recently reported theoretical studies of the reaction pathways of the addition of [OsO 2 (NH) 2 ] to ethylene. [5] The calculations predict that the three possible [3+2] addition reactions are kinetically and thermodynamically favored over the two [2+2] additions, and that the diamination should be the most favored reaction. Pioneering experimental studies of the diamination of olefins with osmium trisimido compounds [OsO (NR) 3 ] have recently been reported by MuÇiz.…”
Section: Introductionmentioning
confidence: 98%
“…The introduction of an imido group in OsO 2 (NH) 2 does not change the overall profile of the reaction. Deubel and Muñiz [4] reported that the three [3+2] addition reactions of ethylene which are possible for the system are clearly favoured over the [2+2] reactions. The authors predicted that the calculated activation barriers decrease with the order O/O > O/NH > NH/NH.…”
Section: Introductionmentioning
confidence: 98%
“…Various theoretical studies [1] have shown that the addition of olefins to OsO 4 initiates with a concerted [3+2] reaction rather than through a two-step process with initial [2+2] addition across an Os=O double bond. Subsequent work [2] has indicated that other metal oxides such as RuO 4 and ReO 3 − also prefer a [3+2] mechanism over a [2+2] reaction [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] These reagents induce a completely chemoselective reaction in favour of diamination [2] and lead to monomeric osmium-diamine chelates with an unprecedented stability ( Figure 1). [3] The inherent properties of these products prompted us to examine whether or not such compounds themselves could act as catalyst precursors for oxidation chemistry.…”
mentioning
confidence: 99%